2009
DOI: 10.1089/lap.2009.0117
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Management of Intussusception in Pediatric Patients

Abstract: We conclude that laparoscopy is a reasonable approach to pediatric intussusception, even in the event when bowel resection is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 9 publications
1
20
1
3
Order By: Relevance
“…Indications for immediate resection in nine patients included: mass 3 (3), Meckel's (3), necrotic bowel (1), enteric duplication (2). Indication for resection after successful manual reduction in 15 patients included: mass (3), Meckel's (5), necrotic bowel (6), enteric duplication (2) noting that one child had both a Meckel's and an enteric duplication.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indications for immediate resection in nine patients included: mass 3 (3), Meckel's (3), necrotic bowel (1), enteric duplication (2). Indication for resection after successful manual reduction in 15 patients included: mass (3), Meckel's (5), necrotic bowel (6), enteric duplication (2) noting that one child had both a Meckel's and an enteric duplication.…”
Section: Resultsmentioning
confidence: 99%
“…[2] However, the question of whether or not to resect is often not obvious and has not been studied, to our knowledge. Certainly, there are clear-cut findings that warrant intestinal resection such as frank necrosis, malignant lead point, or other pathologic lead points that predispose to recurrent intussusception.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple recent studies have shown that laparoscopy offers a safe and cost effective alternative to the open procedure with superior cosmetic results [24][25][26][27]. The intracorporeal reduction was achieved by a combination of gentle traction of the distal intussusceptum with simultaneous squeezing of the intussuscepiens as described by Fraser et al [28]. Some authors argue that laparoscopic reduction carries the risk of serosal tears and bowel perforation, necessitating conversion to open surgery with associated increased operative time and subsequently higher morbidity and longer hospital stay [25].…”
Section: Discussionmentioning
confidence: 99%
“…Le taux de succès de la laparoscopie est passé de 57 % en 1997 à 91 % en 2009, et le taux de conversion de 43 à 9 % [97]. Le risque de conversion est lié au délai entre la prise en charge et le début des symptômes, à l'existence d'une cause locale favorisante ou d'une nécrose intestinale [93].…”
Section: Traitement Chirurgicalunclassified